1997
DOI: 10.1051/jp4:1997424
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Magnetoplasmas in Electronegative Gases

Abstract: Discharges in electronegative gases are routinely used for the sub-micron etching of thin films in the microelectronics industry. Because of the strong electronegative character of these gases, negative ions constitute a signifiant fraction of the charged particles content of the discharge. The presence of these negative charge carriers affects the whole behavior of the discharge and, in particular, its electron power balance. This article compares a few characteristics of a high-density plasma produced either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
(10 reference statements)
1
4
0
Order By: Relevance
“…enhanced by a factor of 2 as pressure increases from 0.4 to 0.8 mTorr. 16 Therefore, the agreement between model and experiments for both pressures further validates the proposed model. Thus, besides the qualitative description of the key phenomena involved in the etching process, the model quantitatively describes the simultaneous dependence of the etch rate on ion energy and on ion and reactive neutral fluxes, provided S n and A sat are known.…”
Section: ͑6͒supporting
confidence: 71%
“…enhanced by a factor of 2 as pressure increases from 0.4 to 0.8 mTorr. 16 Therefore, the agreement between model and experiments for both pressures further validates the proposed model. Thus, besides the qualitative description of the key phenomena involved in the etching process, the model quantitatively describes the simultaneous dependence of the etch rate on ion energy and on ion and reactive neutral fluxes, provided S n and A sat are known.…”
Section: ͑6͒supporting
confidence: 71%
“…The application-orientated research on TWSDs led to introducing changes of the shape of the discharge vessels aiming at reaching large area discharge production [166,167] as well as to inventing new types of launchers for planar discharges [168][169][170][171][172][173][174][175][176][177][178][179][180][181][182][183] and short tubular discharges [184][185][186][187][188][189][190][191][192] and also new launchers for discharge production in the microwave range [193]. Many possibilities for the use of TWSDs for surface processing and film deposition [12,149,[194][195][196][197][198][199][200][201][202][203][204][205][206][207][208][209]…”
Section: Travelling Wave-sustained Discharges: Brief History and Topimentioning
confidence: 99%
“…In this context, we have carried out a rather exhaustive experimental study which comprises the determination of basic SF 6 plasma characteristics as well as some elements of plasma chemistry. Some results of this study have already been reported [5,[14][15][16][17]. In this paper, we present the first detailed spatially resolved measurements of the positive ion densities and electron temperatures obtained in this surface-wave magnetoplasma reactor, when operated with SF 6 and Ar as well as SF 6 /Ar mixtures.…”
Section: Introductionmentioning
confidence: 54%